STUDI PENGAMATAN KUALITAS AIR LINGKUNGAN TAMBAK INTENSIF UDANG VANNAMEI (LITAPENAEUS VANNAMEI) DALAM FAKTOR TERJADINYA PENYAKIT WHITE SPOT SYNDROME VIRUS (WSSV) DAN INFECTIOUS MYO NECROSIS VIRUS (IMNV) - Frans Yudistira; Anis Zubaidah; Hariyadi Hariyadi (IJOTA (Indonesian Journal of Tropical Aquatic), 2024)
Vannamei shrimp (Litopenaeus vannamei) culture frequently faces serious disease outbreaks caused by White Spot Syndrome Virus (WSSV) and Infectious Myonecrosis Virus (IMNV), resulting in significant economic losses in shrimp farming. Environmental conditions, particularly water quality, are considered important factors influencing the emergence and spread of viral diseases in aquaculture systems. Therefore, this study aimed to identify the water quality factors associated with the occurrence of WSSV and IMNV in vannamei shrimp ponds located within the same farming environment. This research was conducted at two different vannamei shrimp farming companies located in North Lombok Regency. The study used a survey method through interviews with farm managers and analysis of secondary water quality data. The observed water quality parameters included salinity, nitrate, nitrite, and ammonia levels. Data analysis was performed using an independent sample t-test to evaluate differences in IMNV occurrence between the two companies based on water quality conditions. The results showed that four pond units were indicated to be affected by IMNV, namely pond 2 in Company A and ponds 1, 2, and 3 in Company B. Several water quality parameters in Company B during December 2019, including salinity, nitrate, nitrite, and ammonia, exceeded the standards established in SNI 01-8037-2014 and were suspected to contribute to the initial emergence of IMNV. Statistical analysis using the independent sample t-test showed no significant difference between Companies A and B regarding IMNV occurrence based on water quality parameters (p = 0.898 > 0.05). In conclusion, water conditions and water quality play a crucial role in maintaining shrimp health and may directly or indirectly influence the occurrence of viral diseases in vannamei shrimp culture systems.